Antimicrobial activity and stability of protonectin with D‐amino acid substitutions. (16th March 2017) - Qiu, Shuai; Zhu, Ranran; Zhao, Yanyan; An, Xiaoping; Jia, Fengjing; Peng, Jinxiu; Ma, Zelin; Zhu, Yuanyuan; Wang, Jiayi; Su, Jinhuan; Wang, Qingjun; Wang, Hailin; et al.
Abstract : The misuse and overuse of antibiotics result in the emergence of resistant bacteria and fungi, which make an urgent need of the new antimicrobial agents. Nowadays, antimicrobial peptides have attracted great attention of researchers. However, the low physiological stability in biological system limits the application of naturally occurring antimicrobial peptides as novel therapeutics. In the present study, we synthesized derivatives of protonectin by substituting all the amino acid residues or the cationic lysine residue with the correspondingD ‐amino acids. Both theD ‐enantiomer of protonectin (D ‐prt) andD ‐Lys‐protonectin (D ‐Lys‐prt) exhibited strong antimicrobial activity against bacteria and fungi. Moreover, D ‐prt showed strong stability against trypsin, chymotrypsin and the human serum, whileD ‐Lys‐prt only showed strong stability against trypsin. Circular dichroism analysis revealed thatD ‐Lys‐prt still kept typical α‐helical structure in the membrane mimicking environment, whileD ‐prt showed left hand α‐helical structure. In addition, propidium iodide uptake assay and bacteria and fungi killing experiments indicated that allD ‐amino acid substitution or partiallyD ‐amino acid substitution analogs could disrupt the integrity of membrane and lead the cell death. In summary, these findings suggested thatD ‐prt andD ‐Lys‐prt might be promising candidate antibiotic agents for therapeutic application against resistant bacteria and fungi infection. Copyright © 2017 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Both the all‐D ‐amino acid‐substituted derivative of protonectin (D ‐prt) andD ‐lysine‐substituted derivative of protonectin (D ‐Lys‐prt) exhibited potent antimicrobial activity against bacteria and fungi.D ‐prt showed strong stability against trypsin, chymotrypsin and the human serum, whileD ‐Lys‐prt only showed strong stability against trypsin.